Rotational stiffness of drum deployed thin-walled open tubular booms. (May 2020) - Shore, Jason; Viquerat, Andrew; Richardson, Guy; Aglietti, Guglielmo
Abstract: Tape springs are a type of thin-walled deployable boom that are used extensively in the space industry to deploy sensors, drag sails and antennas. When a tape spring is stowed it coils into a cylindrical shape and so deployment drums are manufactured as cylinders to match. The consequence of this is that when the tape spring is deployed a portion of the cross section remains flat against the cylindrical drum. This has the effect of reducing the stiffness of the tape spring. In this paper a Finite Element (FE) model is presented to capture this reduction. An experimental method for validating the FE model is also presented on which Beryullium-Copper (BeCu) and glass fibre polypropylene (PP) composite tape springs were tested. The FE model is able to predict the rotational stiffness of the BeCu tape springs more accurately than the composite tape springs. The disagreement in the case of the composite tape springs is attributed to inaccuracies in the available data for the mechanical properties, and the assumption that the tape spring does not compress through the thickness. Increasing the drum length has been shown to decrease the rotational stiffness due to increased flattening at the root. BeCu tape springs show an increase of 82% in the rotational stiffness when the flattened drum region reduces from 90% to 30% of the tape springs' width. Glass fibre PP tape springs with a layup of [ ± 34 ∘ f/0°/ ± 34 ∘ f] show an increase of 65% when the drum length percentage reduces from 82% to 27%. A parametric study showed that the rotational stiffness can be significantly improved with the introduction of local root reinforcing plies. Highlights: A finite element model of a tape spring is presented Partial flattening and restraining of the tape reduces the rotational stiffness Rotational stiffness is linear with respect to the flattened tape spring percentage The rotational stiffness is a strong function of the longitudinal modulus Introducing plies at the root of the tape spring increases the rotational stiffness